OPTIMIZATION OF STRATEGY FOR THE PREVENTION OF ALLERGIC DISEASES IN CHILDREN - L. A. Lityaeva; S. Yu. Nosyreva; D. R. Kushkenbaeva (LLC "Diagnostics and Vaccines", 2017)
The purpose of the study is to determine of the effectiveness of different models of primary prevention of allergic diseases in children of the risk group (24 pairs-with perinatal prophylaxis, other 24 - postnatal) and influences the optimization of the intestinal microbiota on the histamin release. The advantages of the perinatal primary prevention of allergic diseases in children. It is more effective in reducing the incidence of allergic diseases (23% in perinatal, 56% at postnatal) and the severity of skin Allergy in the first year of life (perinatal prevention 100% - mild form, in postnatal - 88% mild form, 12% moderate form). Perinatal prevention of immunomodulator and synbiotic containing strain of L. acidophilus NK-1, with a certain diaminoksidazy activity, contributes to the reduction of the quantitative content and species composition of the intestinal microorganisms with high histamin release, positively affecting the pool of free histamine in infants.